1986
DOI: 10.1172/jci112270
|View full text |Cite
|
Sign up to set email alerts
|

A myeloma paraprotein with specificity for platelet glycoprotein IIIa in a patient with a fatal bleeding disorder.

Abstract: Impaired platelet aggregation, normal shape change, and agglutination and normal ATP secretion and thromboxane synthesis in response to high concentrations of thrombin or arachidonic acid were found in a patient with multiple myeloma and hemorrhagic tendency. The purified IgG1 kappa or its F(ab'}2 fragments induced similar changes when added in vitro to plateletrich plasma from normal subjects. In addition, the paraprotein inhibited adhesion to glass microbeads, fibrin clot retraction, and binding of radiolabe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
1

Year Published

1991
1991
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 97 publications
(51 citation statements)
references
References 44 publications
0
50
1
Order By: Relevance
“…51,52 On the other hand, GT-like functional defects caused by anti-GPIIb-IIIa autoantibodies without thrombocytopenia have been reported in some patients with bleeding tendency. [53][54][55][56][57][58] Although analysis of platelet function in chronic ITP has been limited by concomitant thrombocytopenia, our sensitive ELISA suggested that in most patients, PA anti-GPIIbIIIa autoantibodies have the potential to inhibit fibrinogen binding and may contribute to functional defects in this disorder. In addition, it has recently been suggested that antibodies directed against conformational epitopes on GPIIb-IIIa are more pathogenic than other platelet antibodies and act through an Fc-dependent mechanism in an animal model.…”
Section: Discussionmentioning
confidence: 99%
“…51,52 On the other hand, GT-like functional defects caused by anti-GPIIb-IIIa autoantibodies without thrombocytopenia have been reported in some patients with bleeding tendency. [53][54][55][56][57][58] Although analysis of platelet function in chronic ITP has been limited by concomitant thrombocytopenia, our sensitive ELISA suggested that in most patients, PA anti-GPIIbIIIa autoantibodies have the potential to inhibit fibrinogen binding and may contribute to functional defects in this disorder. In addition, it has recently been suggested that antibodies directed against conformational epitopes on GPIIb-IIIa are more pathogenic than other platelet antibodies and act through an Fc-dependent mechanism in an animal model.…”
Section: Discussionmentioning
confidence: 99%
“…Aggregation of platelets in platelet-rich plasma, TXB2 synthesis, and ATP secretion in response to 1 or 5 U/ml thrombin, preparation of suspensions ofwashed platelets, purification and labeling of human fibrinogen, thrombin-dependent fibrinogen binding, and analysis ofthe binding data were performed as previously described (23). For studies on the sensitivity of platelets to aggregating agents, the AC50 was calculated.…”
Section: Methodsmentioning
confidence: 99%
“…Rarely, in vitro investigations have confirmed that bleeding and abnormal platelet aggregation studies were due to a paraprotein-specific qualitative platelet defect such as binding to GPIIIa. 10 Over 450 cases of acquired von Willebrand factor (VWF) deficiency, representing multiple underlying disorders and probable mechanisms, have been published or summarized in an international registry of acquired von Willebrand syndrome (AVWS). 11 Although an accurate estimate of the incidence of AVWS is not available, clinically apparent cases are uncommon.…”
Section: Disorders Of Primary Hemostasis and Acquired Von Willebrand mentioning
confidence: 99%